2007
DOI: 10.1104/pp.107.096727
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of a Soybean ATP-Binding Cassette-Type Transporter in the Secretion of Genistein, a Signal Flavonoid in Legume-Rhizobium Symbiosis

Abstract: Legume plants have an ability to fix atmospheric nitrogen into nutrients via symbiosis with soil microbes. As the initial event of the symbiosis, legume plants secrete flavonoids into the rhizosphere to attract rhizobia. Secretion of flavonoids is indispensable for the establishment of symbiotic nitrogen fixation, but almost nothing is known about the membrane transport mechanism of flavonoid secretion from legume root cells. In this study, we performed biochemical analyses to characterize the transport mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
141
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 181 publications
(149 citation statements)
references
References 46 publications
(53 reference statements)
4
141
1
3
Order By: Relevance
“…However, rhizodeposition of isoflavonoids occurs through mechanisms other than root exudation as well, e.g., root border cells (Hawes et al 2000). Therefore, silencing components of root exudation machinery (e.g., ABC transporters [Brechenmacher et al 2009;Sugiyama et al 2007]) might not result in efficient depletion of isoflavonoids in rhizodeposits. Similarly, the use of adsorbents might disrupt quorum signals between bacteria and cause nonspecific modifications in root-surface microbial communities and exert unpredicted, indirect impacts on nontarget organisms, including the plant producing the flavonoids (Hassan and Mathesius 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, rhizodeposition of isoflavonoids occurs through mechanisms other than root exudation as well, e.g., root border cells (Hawes et al 2000). Therefore, silencing components of root exudation machinery (e.g., ABC transporters [Brechenmacher et al 2009;Sugiyama et al 2007]) might not result in efficient depletion of isoflavonoids in rhizodeposits. Similarly, the use of adsorbents might disrupt quorum signals between bacteria and cause nonspecific modifications in root-surface microbial communities and exert unpredicted, indirect impacts on nontarget organisms, including the plant producing the flavonoids (Hassan and Mathesius 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Using plasma membrane vesicles prepared from soybean roots, these roots were shown to possess an ATPdependent transporter that functions in the secretion of genistein into the rhizosphere (Sugiyama et al 2007). Biochemical transport assays using various inhibitors have suggested that an ABC transporter is the primary candidate for this process.…”
Section: Secretion Of Flavonoids From Plant Rootsmentioning
confidence: 99%
“…Isoflavones play important roles as signal molecules for inhibiting pathogen attacks (Lozovaya et al, 2007;Zabala et al, 2006) and for plant-microbe symbiotic interactions (Subramanian et al, 2006;Sugiyama et al, 2007). Genistin and daidzin is initiated by the conversion of the essential amino acid L-phenylalanine into p-Coumaroyl-CoA.…”
Section: Soybean Composition and Isoflavone Biosynthesismentioning
confidence: 99%